Kondisi Kerja Layak Pekerja Media di Magetan - Rachma Ukhty, Berlian Fika (Jurnal Studi Jurnalistik, 2025)
This research aims to provide an overview of the decent work conditions of media workers, especially journalists, in the rapidly developing era of digital technology and communication. The concept of decent work is defined as working conditions that provide workers with freedom, fairness, security, and respect for human dignity. By adopting several indicators of decent work for media workers from previous research, this study uses 6 indicators to determine the conditions of decent work, namely: employment relationship/employment agreement system; wage/salary system; fulfillment of employment rights (benefits); financial condition; equal opportunities and treatment in employment; and social security. This research uses an online survey as a data collection method and descriptive analysis to explain the findings. A total of 46 respondents were journalists working in Magetan Regency. The results showed that the indicators of employment relationship/employment agreement system; wage/salary system; fulfillment of employment rights (benefits) and social security have not been fulfilled optimally. Thus, media workers, especially journalists in Magetan Regency have not received decent working conditions. Keywords⎯ decent working conditions, media workers, journalism, journalists